The Effect of Work-Family Conflict and Family-Work Conflict on Individual Job Performance in Nurses - Fatmanur Karaman; Ülkü Baykal; Seyhan Çerçi (Sağlık ve Hemşirelik Yönetimi Dergisi)
Aim: This study was conducted to determine the effect of work-family and family-work conflict levels of nurses on their individual job performance. Method: The sample of this descriptive and correlational design study consisted of 305 nurses. Data were collected online using the Personal Information Form, Work-Family Conflict Scale, Family-Work Conflict Scale and Individual Job Performance Scale. Descriptive statistics, correlation analyses and multiple linear regression analyses were performed. Results: The mean age of the nurses was 32.66 years, 83.6% were female, 59.3% were married, and 48.5% had undergraduate education. The mean total scores of the scale were 30.12 in Work-Family Conflict Scale, 24.41 in Family-Work Conflict Scale and 54.26 in Individual Job Performance Scale. There is a very weak negative significant relationship between work-family conflict (r: -0,121) and family-work conflict (r: -0,170) and individual job performance of nurses (p<0,05). In addition, working at university (β: 0,297) and private (β: 0,166) hospitals positively (p<0,05), Family-Work Conflict negatively (β: -0,171), and Work-Family Conflict did not have a significant effect (p>0,05) (R2: 0,088; F: 8,328; p<0,001). Conclusion: Nurses had a high perception of work-family conflict, a low perception of family-work conflict and a high perception of individual job performance. As the level of family-work conflict increased in nurses, the perception of work performance was negatively affected. Working in a university hospital and a private hospital positively affected nurses' perception of work performance. In this respect, conflict management training can be given to nurses to reduce their conflicts and vocational training can be given to increase their job performance.